Multifunctional mixed analog/digital signal processor based on integrated photonics - Yichen Wu; Qipeng Yang; Bitao Shen; Yuansheng Tao; Xuguang Zhang; Zihan Tao; Luwen Xing; Zhangfeng Ge; Tiantian Li; Bowen Bai; Haowen Shu; Xingjun Wang (Opto-Electronic Science, 2024)
Photonic signal processing offers a versatile and promising toolkit for contemporary scenarios ranging from digital optical communication to analog microwave operation. Compared to its electronic counterpart, it eliminates inherent bandwidth limitations and meanwhile exhibits the potential to provide unparalleled scalability and flexibility, particularly through integrated photonics. However, by far the on-chip solutions for optical signal processing are often tailored to specific tasks, which lacks versatility across diverse applications. Here, we propose a streamlined chip-level signal processing architecture that integrates different active and passive building blocks in silicon-on-insulator (SOI) platform with a compact and efficient manner. Comprehensive and in-depth analyses for the architecture are conducted at levels of device, system, and application. Accompanied by appropriate configuring schemes, the photonic circuitry supports loading and processing both analog and digital signals simultaneously. Three distinct tasks are facilitated with one single chip across several mainstream fields, spanning optical computing, microwave photonics, and optical communications. Notably, it has demonstrated competitive performance in functions like image processing, spectrum filtering, and electro-optical bandwidth equalization. Boasting high universality and a compact form factor, the proposed architecture is poised to be instrumental for next-generation functional fusion systems.